The Impact of Organizational Commitment and Work Discipline on Work Motivation and Its Implications on the Performance of Village Government Employees in Barangin District, Sawahlunto City - Aima, M. Havidz; Qomaria, Evra (UPI YPTK Journal of Business and Economics, 2024)
This study aims to explore the influence of organizational commitment and work discipline on work motivation and its implications for the performance of Village Government Employees in Barangin District, Sawahlunto City. The methodology employed includes multiple linear regression analysis and path analysis, with questionnaires distributed to 87 respondents. Data processing was conducted using Smart PLS 4.0. The findings indicate that organizational commitment significantly affects work motivation among village government employees in Barangin District, Sawahlunto City. Furthermore, organizational commitment also significantly impacts the performance of these employees. Additionally, work discipline significantly influences both work motivation and employee performance in the aforementioned district. Work motivation, in turn, significantly affects employee performance. Moreover, organizational commitment and work discipline together exert a significant influence on work motivation. When combined with work motivation, organizational commitment and work discipline significantly influence the performance of village government employees. Lastly, work motivation mediates the influence of organizational commitment and work discipline on employee performance in Barangin District, Sawahlunto City.